The relationship between defense R&D investment and the autonomy of the national defense industry - Hutagaol, Immanuel A.; Iswati, Sri; Haetami , Haetami (Journal of Economics and Business Letters, 2025)
This study analyzes the relationship between research and development (R&D) investment in the defense sector and the autonomy of Indonesia’s national defense industry. Employing a qualitative approach based on a literature review and document analysis, this study examines theoretical frameworks, policy instruments, and empirical practices in Indonesia and selected comparator countries, including the roles of institutions such as KKIP, BRIN, and the Ministry of Defense. The main findings indicate that defense R&D investment plays a critical role in building technological capacity, strengthening domestic supply chains, increasing the local content ratio (TKDN), and promoting import substitution and technology transfer. However, key challenges persist, including limited funding, policy fragmentation, and underdeveloped human resources in defence R&D. Case studies of state-owned defense enterprises (PT Pindad, PT PAL, PT DI) illustrate the dynamics of innovation, international collaboration, and resulting economic multiplier effects. The study concludes that the success of defense R&D investment is highly dependent on policy synergy, sustainable funding, a robust innovation ecosystem, and developing high-quality human capital. Policy recommendations emphasize the need to increase R&D budget allocations, optimize triple helix collaboration, and implement regulatory reforms to accelerate the autonomy of the national defense industry.